Vivid Tumor Imaging Utilizing Liposome-Carried Bimodal Radiotracer - Kim, Jonghee (American Chemical Society, 2014)
[Image: see text] By developing a new bimodal radioactive tracer that emits both luminescence and nuclear signals, a trimodal liposome for optical, nuclear, and magnetic resonance imaging is efficiently prepared. Fast clearance of the radiotracer from reticuloendothelial systems enables vivid tumor imaging with minimum background.